51‐4: Near‐Eye Display for Vision Correction with Large FOV. Issue 1 (2nd June 2017) - Wu, Yishi; Chen, Chao Ping; Zhou, Lei; Li, Yang; Yu, Bing; Jin, Huayi
Abstract : We propose a see‐through near‐eye display capable of visual correction for ‐3.00‐diopter myopia. Our solution features a freeform waveguide, which integrates a corrective lens and multiplexed volume holograms. Its key performance including diffraction efficiency, field of view, modulation transfer function, and distortion has been studied.